THE COMMUNITY OF POLYCHAETA AT THREE SEAGRASS BEDS IN PARI ISLAND OF JAKARTA - - Hadiyanto (Pusbindiklat - LIPI, 2012)
The community of polychaeta at three seagrass beds (Thalassia hemprichii, Thalassia hemprichii-Cymodocea rotundata-Enhalus acoroides, Enhalus acoroides) in Pari Island of Jakarta was studied on June 2010. Three core samples (0.02 m2) were randomly collected from three seagrass beds. A total of 27 species belonging to 14 families was found, and the most of dominant species was Mediomastus californiensis (21–50% of the total individuals). T. hemprichii was the highest of value of H’ and J’ (2.301 and 0.926 respectively), while E. acoroides was the highest of value of D (0.282), so the community of polychaeta at T. hemprichii was more stable than other seagrass beds.